Prarancangan Pabrik Metil Laktat Dari Asam Laktat Dan Metanol Kapasitas 15.000 Ton/Tahun - Setyawan, Tunjung, Eni Budiyati, S.T., M.Eng, Hamid Abdillah, S.T., M.T (2016)
ABSTRACT Methyl Lactate is a product that is used as a synthetic raw material in the fields of pharmaceutical, perfume raw materials (fragrance) in the field of cosmetics and in the field of electronic materials industry as a cleaner, glass cleaner, solvent printing, plastic solvents, paint solvents and materials for insecticides. To meet domestic needs and their export opportunities that are still open, the plant is designed with a capacity of Methyl Lactate 15,000 tons / year with the raw material of Lactic Acid and Methanol. The factory is planned to stand in Bontang, East Kalimantan in 2020. The process of making methyl lactate used in a reactor CSTR (Continuous Stirred Tank Reactor), which serves for reacting lactic acid material from a factory in China and Musashino Chemical Methanol from PT. Kaltim Methanol Industry in Bontang, East Kalimantan with sulfuric acid catalyst of PT. Indonesian Acids Industry in Bekasi, East Jakarta, on a liquid-liquid phase, with the irreversible nature of the reaction, exothermic, isothermal, non-adiabatic reactor at a temperature of 100 ° C and a pressure of 2.4 atm. Conversion for this reaction was 75.75%. Distillation tower that consists of four used to purify the product of the reactor in order to obtain methyl lactate purity of 98.28% with 1.72% impurities 0.000081% Lactic Acid and Sulphuric Acid. Lactic acid requirement for this plant as much as 1428.79 kg / h and needs Methanol as much as 512.23 kg / hour. Products such as methyl lactate as much as 1861.34 kg / hour. A support unit includes unit procurement process plant water, steam, compressed air, electricity and fuel. The factory is also supported by laboratories that control the quality of raw materials and products as well as plant waste material. River water as cooling needs of 69041.36 kg / hour, the supply of steam at 1805.16 kg / h, the compressed air requirement of 5.26 kg / hour, demand for electricity is obtained from the PLN and one as a backup generator, the solar requirement by 0 , 22 m3 / h. The form of the selected company is a Limited Liability Company (PT). Systems based on the division of employees working hours of employees shift and non-shift which numbered 171 people. Methyl Lactate factory is at low risk with a fixed capital of Rp 300,603,870,789.76 and working capital of Rp 100,127,930,222.16. Profit before tax of Rp 96,539,200,568.50 per year and after taxes amounting to Rp 67,577,440,397.95 per year. From the calculations, the value of the Return On Investment (ROI) before tax after tax 32.12% and 22.48%. Pay Out Time (POT) before tax is 2.37 years and 3.08 years after tax. Break Even Point (BEP) amounted to 44.4% and Shut Down Point (SDP) amounted to 23.79%. Discounted Cash Flow (DCF) of 41.5%. Based on the calculation of technical and economic evaluation has been done, the plant Methyl Lactate with a capacity of 15,000 tons per year eligible to be established. Keywords: lactic acid, esterification, methyl lactate